2012
DOI: 10.1111/j.1463-1326.2012.01569.x
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin, a novel potent and selective SGLT‐2 inhibitor, improves glycaemic control alone and in combination with insulin in streptozotocin‐induced diabetic rats, a model of type 1 diabetes mellitus

Abstract: Empagliflozin reduced blood glucose levels in a T1DM animal model. Empagliflozin combined with low-dose insulin showed comparable glucose-lowering efficacy to treatment with high-dose insulin. Our data suggest that empagliflozin is an efficacious adjunctive-to-insulin therapy with the clinical potential for the treatment of T1DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 33 publications
(45 reference statements)
7
55
0
Order By: Relevance
“…The increase in insulin plasma levels in ZDF rats with different SGLT2i drugs is well documented [25,[46][47][48][49]. Of importance is that empagliflozin was shown to lower blood glucose levels (thereby sparing insulin) in a preclinical model of streptozotocin-induced type 1 diabetes [50] and also in human studies [51,52]. SGLT2i treatment appears to be highly efficient in preventing glucotoxicity, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in insulin plasma levels in ZDF rats with different SGLT2i drugs is well documented [25,[46][47][48][49]. Of importance is that empagliflozin was shown to lower blood glucose levels (thereby sparing insulin) in a preclinical model of streptozotocin-induced type 1 diabetes [50] and also in human studies [51,52]. SGLT2i treatment appears to be highly efficient in preventing glucotoxicity, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the important studies demonstrated that empagliflozin enhances the urinary glucose excretion with concomitant reductions in the fasting and postprandial glucose levels and glycated hemoglobin (HbA1c) in Zukar Diabetic Fatty (ZDF) rats [47,48]. One important study [49] showed the significance of combinatorial therapy of empagliflozin with insulin in type-1 diabetes mellitus (T1DM) rats. The research work clearly revealed that addition of empagliflozin to insulin pre-treated rats causes prolonged reductions in hyperglycemia, without any episode of hypoglycemia.…”
Section: Empagliflozinmentioning
confidence: 99%
“…Empagliflozin increased urinary glucose excretion (UGE) and improved glycemic control in streptozotocin-induced T1D rats. 10,11 In T1D mice, empagliflozin treatment significantly improved glucose tolerance with improvements in mRNA and serum insulin levels. 10 The authors hypothesized that empagliflozin may help in the preservation of β-cell mass, evidenced by reduction in β-cell apoptosis and stimulation of β-cell proliferation, possibly due to protection of β-cells from glucotoxicity-induced oxidative stress.…”
Section: Clinical Evidence With Sodium-glucose Co-transporter-2 Inhibmentioning
confidence: 99%
“…The prevalence of overweight and obesity among newly diagnosed T1D subjects was 21-22% in the [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] year age group in the Pediatric Diabetes Consortium and the SEARCH for Diabetes in Youth study. 1,2 This has been attributed to a general worldwide increase in prevalence of obesity and similar risk factors such as family history, ethnicity, and sedentary lifestyle may be contributory.…”
mentioning
confidence: 99%